2013
DOI: 10.2478/tumor-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

Selective radiosensitization of hypoxic cells using BCCA621C: a novel hypoxia activated prodrug targeting DNA-dependent protein kinase

Abstract: Tumour hypoxia presents a barrier to conventional chemotherapy and radiation therapy. To combat hypoxic cells a number of hypoxia modifying treatments are currently in development. In this study we assessed the potential for inhibiting DNA double strand break repair in hypoxic cells by targeting DNA-dependent protein kinase (DNA-PK) and we report the synthesis and in vitro efficacy of BCCA621C (1), a hypoxia activated inhibitor of DNA-PK. We found that DNA-PK deficient hypoxic cells are radiosensitive compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…However, only little is known about the effect of DNA-PKc inhibition on the radiosensitivity of hypoxic cells. Lindquist and colleagues described radiosensitivity effects with photon irradiation of DNA-PK deficient mouse embryonic fibroblast cells (SCID/st) under normoxic and hypoxic conditions compared to isogenic DNA-PK wildtype cells (CB.17) and that DNA-PK inhibition in combination with photon irradiation decreases the clonogenic survival of both oxic and hypoxic cells [ 31 ]. They suggested that impairment of DNA-PK radiosensitizes independently of cellular oxygen status.…”
Section: Discussionmentioning
confidence: 99%
“…However, only little is known about the effect of DNA-PKc inhibition on the radiosensitivity of hypoxic cells. Lindquist and colleagues described radiosensitivity effects with photon irradiation of DNA-PK deficient mouse embryonic fibroblast cells (SCID/st) under normoxic and hypoxic conditions compared to isogenic DNA-PK wildtype cells (CB.17) and that DNA-PK inhibition in combination with photon irradiation decreases the clonogenic survival of both oxic and hypoxic cells [ 31 ]. They suggested that impairment of DNA-PK radiosensitizes independently of cellular oxygen status.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst HAPs designed to release DNA-damaging species are still being developed, other HAPs have been designed to release inhibitors of DNA damage response pathways [ 123 , 124 ]. Release of the Chk1/Aurora A inhibitor CH-01 (Fig.…”
Section: Novel Haps In Preclinical Developmentmentioning
confidence: 99%
“…Similarly, attachment of a DNA-PK inhibitor to a nitroimidazole hypoxia trigger group led to inactivation of the complex (BCCA621C, Fig. 9 ) and no cytotoxic activity under aerobic conditions was reported [ 124 ]. Under severe hypoxia, however, the inhibitor was released and was able to radiosensitise hypoxic H460 cells in vitro with a sensitiser enhancement ratio of 1.85.…”
Section: Novel Haps In Preclinical Developmentmentioning
confidence: 99%
“…Future studies of modifying the radiation response of hypoxic cells in tumors with existing drugs or with newer approaches such as improving oxygen availability in tumors with metformin treatment to reduce oxygen consumption 134 or hypoxia-activated drugs which target DNA damage response pathways 135,136 , should be conducted with prospective hypoxia measurements and include measurements made during the course of therapy. Using techniques for hypoxia measurement that effectively address issues of heterogeneity are required for such studies.…”
Section: Predicting Radiation Responsementioning
confidence: 99%